Irrigation scheduling: reference manual - Raes, D.; Shrestha, Nirman (International Water Management Institute, 2025)
The Irrigation Scheduling Reference Manual provides in-depth information for effectively managing agricultural water use through irrigation scheduling. This manual serves as reference material for the Standard Operating Procedure (SOP) for Developing Irrigation Scheduling.